Selain Kurikulum Baru (201 3), Apalagi Agenda Pendidikan Kita: Kajian Paradigma Manajemen Pendidikan - Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2013)
In educational field, curriculum is not a new part, moreover it is undoubtely used in formal education. However, the changing of its exsistence and content always brings both positive and negative side for the teachers, learners and other elements of the school or institution. Ideally, the goverment, an agent who decides the curriculum, should given a chance tor the teachers to critcize every curriculum which is implemented or used in the school and institution in order to broader the comprehension of them in elaborating the curriculum. After the revision in 2013 about curriculum, in educational management point of view, there are many agendas need to be concerned more such as endeavoring and developing an educator's quality of teaching. Curriculum is simile to a surface of a money. Teacher must understand and accept the curriculum content which its changing in teaching methods and techniques included in, hence the classroom activity can be successfully done. ln contra st, the unreachable aspect of the teacher in intepreting and elaborating the curriculum can create the unsuccessful result of classroom activity. In conclusion, the all aspect of the curri culum implementation to classroom activity depend s on the teacher